The Synthesis Study of Sulfanilamide Analogue from Natural Substances Papaverine Alkaloid - I Made Sudarma; Mulyanto Mulyanto (Jurnal ILMU DASAR, 2008)
The aim of this research was to synthesize sulfanilamide analogue from natural products papaverine alkaloid. Sulfanilamide is known as an antibiotic which has been used for treatment of infection. Theoretically papaverine could be converted to be sulfanilamide analogue by two steps reactions, first sulfonation of papaverine by sulfonic acid to produce sulfonyl chloride and second reaction of with ammoniac to produce. The formation of this product was analyzed by analytical thin layer chromatography and FT-IR. This analysis showed the formation of product quite difficult since the compound was easily reacted with water to form compound. Infrared spectra supported the formation of which showed vibrations at 1153.4 and 1265.2 Cm-1 due to absorption of sulfonyl group and at 3433.1 Cm-1 due to absorption of –OH group.